Early Cretaceous spinicaudatans ("conchostracans") from lacustrine strata of the Sidi Aïch Formation in the northern Chotts range, southern Tunisia: Taxonomy, biostratigraphy and stratigraphic implication. (September 2015) - Boukhalfa, Kamel; Li, Gang; Ben Ali, Walid; Soussi, Mohamed
Abstract: The fossil clam shrimp genus Cratostracus was first described from the Turonian–Coniacian (Upper Cretaceous) Qingshankou Formation in the Jilin and Heilongjiang provinces of China, and it has been found to range down into the Aptian Guantou Formation in Zhejiang Province of southeastern China. Recently, species tentatively attributable to it ( Cratostracus ? cheni ) has been recorded in the well-known Jehol Biota bearing Barremian–lower Aptian (Lower Cretaceous) Yixian Formation in western Liaoning Province of northeastern China. The species described in this paper as Cratostracus ? tunisiaensis sp. nov. was recovered from the Sidi Aïch Formation in the Chotts area of southern Tunisia. Although only tentatively attributed to Cratostracus, its occurrence is consistent with a Barremian (Early Cretaceous) age for the formation. This first direct dating of the Sidi Aïch Formation gives a valuable insight for the stratigraphy of the region and will make it possible to more precisely correlate the different outcrops of the Sidi Aïch Formation. Moreover, the new fossil discovery allows a reconstruction of the paralic ecosystem that characterized the study area during the Barremian. Graphical abstract: Highlights: A new fossil clamp shrimp species is described from non-marine deposits in Tunisia. Biostratigraphic evidence of a Barremian age for the Sidi Aïch Formation in Tunisia. Fossil clam shrimp Cratostracus is recorded for the first time outside China.